Leader selection using Analytical Hierarchy Process (AHP) / Muhammad Hazwan Ahmad Hamdan - Ahmad Hamdan, Muhammad Hazwan (2012)
In world today, making decision is no longer a simple task that can be made easily by a person, a company or a big organization. Analytical Hierarchy Process (AHP) introduces a scientific and a very logical way to assist people on making crucial decision. AHP is a technique that uses hierarchy approach to determine the weight of the objective, criterion and alternative. In this study, AHP technique is use to selecting the best leader among a group of leader. The objective of this project is to make ‘manual’ AHP into ‘computerized’ AHP. That means to build a system that use AHP method. This project is using the actual AHP formulae but reconstruct the techniques into programming language. So those, all the calculation are made by the computer and it also faster than using manual calculation. As a result of this project, the system successfully determines the best candidate to be a leader with the result of comparing and sorting. It is hoped that this project will give benefits to other researcher in order to continue the same research in the same field.